Crescimento da literatura brasileira de doença de Chagas: análise bibliométrica - Caldeira, Paulo da Terra (1974)
Historical outline of Chagas' disease, since its discovery by Carlos Chagas up to currently research areas, in Brazil. Goffman's theory on the works on Chagas' disease and the use of the deterministic model, verifying a growth of the literature after 1933.